Public stockholdings, special safeguard mechanism and state trading enterprises: What’s food security got to do with them? - Díaz-Bonilla, Eugenio (Instituto Interamericano de Cooperación para la Agricultura, 2021)
Food security has been invoked for a variety of trade interventions and in many trade negotiations This chapter focuses on three trade topics for which food security concerns have been mentioned as the rationale (or at least part of it) for their inclusion in the WTO negotiations use: public stockholdings (PSH), the special safeguard mechanism (SSM) and state trading enterprises (STEs).